2016
DOI: 10.1515/ijamh-2016-0076
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine consumption patterns and determinants among adolescents in Serbia

Abstract: Background: The number of adolescents who use caffeine is constantly increasing. As juvenile age is vulnerable, it is reasonable to expect that they will differently perceive reason and react to caffeine use than adults, and be more prone to unwanted physiological and psychological consequences of its consumption. Aim: Analysis of the scope and pattern of caffeine consumption among adolescents in Serbia. Study design: The cross-sectional survey was implemented in the study population of 191 Serbian adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
2
1
3
Order By: Relevance
“…Moreover, a study conducted showed that students did consider caffeine had a major role in increasing their academic performances (13) . In contrast to our study, a study from Serbia revealed that the people were mostly consuming caffeine for the reason of leisure, peer pressure and as a habit (22) . A similar study concluded that the majority of the participants were aware of the health risks that followed caffeine usage especially effects on the heart (23) .…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, a study conducted showed that students did consider caffeine had a major role in increasing their academic performances (13) . In contrast to our study, a study from Serbia revealed that the people were mostly consuming caffeine for the reason of leisure, peer pressure and as a habit (22) . A similar study concluded that the majority of the participants were aware of the health risks that followed caffeine usage especially effects on the heart (23) .…”
Section: Discussioncontrasting
confidence: 99%
“…The same survey reported that caffeine is the most popular substance in the campus with an average of 1106.23-1698.02 mg per week, increasing with year in school 20 . However, in contrast our findings, a study from Serbia revealed that the common reasons for caffeine intake among adolescents were leisure, peer influence and habit 21 . In contrast to general perceptions scientific evidence from different research studies showed no such relationship.…”
Section: Discussioncontrasting
confidence: 99%
“…Coffee drinkers and energy drink users identified the energising effects (e.g., “to stay awake”, “for energy” and “to wake up”) as the main reason for consuming these beverages. This is consistent with previous findings from a Saudi Arabian study ( n = 1006) that adolescent boys ingested coffee “to stay awake” [ 35 ] and energy drinks to “boost energy” [ 35 ]. A qualitative Canadian study ( n = 166) found that energy provision was the main motivating factor regardless of whether they liked the taste of caffeinated beverages [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…Tea was also consumed for the attributes of temperature as well as to relax, suggesting tea drinkers view their tea consumption as habitual rather than for the caffeine content. This is consistent with a Serbian study where adolescents identified their main reason for drinking tea “as a habit” [ 35 ].…”
Section: Discussionsupporting
confidence: 91%